Combined Use of BSC and DEA Methods for Measuring Organizational Efficiency - Aleksandra Bošković; Ana Krstić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Although financial indicators are most often used to measure organizational efficiency, contemporary research suggests that more consideration should be given to non-material factors that can be enveloped by different non-parametric techniques. However, there is no method powerful enough to cover all the relevant aspects of the efficiency problem, i.e. each of them has its advantages and disadvantages. The paper discusses possible combined use of Balanced Scorecard (BSC) method and Data Envelopment Analysis (DEA) in the measurement of organizational efficiency, starting from the deficiencies of the single method use. The main goal of the research in the paper is to show that by combining these methods certain deficiencies in their independent application are eliminated, as well as to indicate the possibilities and limitations, advantages and disadvantages of their combined application. The paper explains that if BSC method is applied first, as a framework for defining goals and performance measures, and then four interactive DEA models are developed, in order to evaluate efficiency in each of the perspectives, relevant synergetic effects will be achieved.
Keywords: D24; D57; M21; 330; Balanced Scorecard; Data Envelopment Analysis; organizational efficiency; combined use of methods; decision support systems